2015
DOI: 10.1681/asn.2014060536
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Function Alters the Relationship between Postoperative Troponin T Level and Death

Abstract: Cardiac troponin T (cTnT), even at low concentrations, is a risk factor for 30-day mortality in patients undergoing noncardiac surgery, but it is uncertain whether that risk is generalizable to patients with poor kidney function. We, therefore, evaluated the relationship between cTnT concentration and kidney function on the outcome of 30-day mortality in a post hoc analysis of a prospective cohort study of patients undergoing noncardiac surgery. cTnT was measured for 3 days after surgery and considered abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Our study confirmed similar results in patients with CKD using the fifth generation hsTnT assay and furthermore demonstrates an increased risk of long-term mortality, which was unclear in patients with severe CKD. Similar to Walsh and colleagues, 36 patients with severe CKD in our cohort were more subject to undergo emergency procedures. Observing the same trend in a larger cohort than ours, suggests that this is a selection bias for which we cannot fully adjust.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our study confirmed similar results in patients with CKD using the fifth generation hsTnT assay and furthermore demonstrates an increased risk of long-term mortality, which was unclear in patients with severe CKD. Similar to Walsh and colleagues, 36 patients with severe CKD in our cohort were more subject to undergo emergency procedures. Observing the same trend in a larger cohort than ours, suggests that this is a selection bias for which we cannot fully adjust.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, they found no interaction between eGFR and postoperative hsTnT. The study by Walsh and colleagues 36 displays the same increased risk of 30-day all-cause mortality between the different strata of CKD when postoperative troponin T was elevated (!0.02 ng ml À1 fourth generation assay) up to CKD with an eGFR !30 ml min À1 1.73 m À2 . Our study confirmed similar results in patients with CKD using the fifth generation hsTnT assay and furthermore demonstrates an increased risk of long-term mortality, which was unclear in patients with severe CKD.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, we could not, for example, adequately study the effect of residual renal function on the observed relationships and test the hypothesis that reduced tubular metabolism is an important determinant of the observed elevation in biomarker concentrations. Second, our epidemiologic study does not address the direct clinical usefulness of the biomarkers in diagnosing acute events, such as cardiac ischemia, although it was recently shown that residual renal function is an important confounder when using TnT for that purpose (45,46). Third, because we measured the circulating biomarkers using commercial ELISA kits, the unknown epitopes of most of these makes any meaningful interpretation difficult.…”
Section: Discussionmentioning
confidence: 99%
“…CKD also has a substantial impact on societal costs, by increasing per se the need for healthcare services [ 3 ] and contributing to work disability [ 4 ]. Further, the consequences of CKD are of importance for many other aspects of healthcare, including the incidence of other comorbidities [ 1 , 5 ] or impairment on the diagnostic accuracy of laboratorial analyses and medical devices [ 6 8 ] dependent on protein or fluid retention by the failing kidneys. Notwithstanding that creatinine is a very common and low-cost assessment in healthcare [ 9 , 10 ], systematic screening programs are lacking and, in most societies, the awareness of CKD among both physicians and patients remains very low [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%